Facile one‐pot preparation of a novel imidazolium‐based monolith by thiol–ene click chemistry for capillary liquid chromatography. Issue 22 (28th November 2016) - Zhang, Peng; Yang, Haiguan; Chen, Tao; Qin, Yuemei; Ye, Fanggui
Abstract: In this work, a novel imidazolium‐based monolith was fabricated through a simple route. With 1‐vinyl‐3‐octadecylimidazolium bromide and ethylene dimethacrylate as monomers, pentaerythritol tetra‐(3‐mercaptopropionate) as crosslinker, AIBN as thermal initiator, the monolith was facilely fabricated by one‐pot thiol–ene click chemistry. The influences of both the content of monomer/crosslinker and porogenic systems on the morphology, and permeability of the monolith were studied. The optimal reaction conditions were used to prepare a homogeneous and permeable monolith. The optimal preparation of monolithic column was characterized by scanning electron microscopy, Fourier transform infrared spectrometry, X‐ray photoelectron spectroscopy, and thermogravimetric analysis. High efficiency and quick separation of alkylbenzenes, styrene and ethylbenzene, polycyclic aromatic hydrocarbon, phenols, anilines, and aromatic acids were achieved. The minimum plate height of this monolith were determined as 11.42 μm for thiourea and 13.26 μm for benzene. All results indicated that thiol–ene click chemistry provides a quick way for the fabrication of imidazolium‐based monolith.